Young Adults, Technology, and Weight Loss: A Focus Group Study. (18th February 2015) - Stephens, Janna; Moscou-Jackson, Gyasi; Allen, Jerilyn K.
Abstract : Overweight and obesity are a major concern in young adults. Technology has been integrated into many weight loss interventions; however little is known about the use of this technology in young adults. The purpose of this study was to explore through focus group sessions the opinions of young adults on the use of technology for weight loss. A total of 17 young adults, between 18 and 25 years of age, participated in three focus group sessions. Major results indicated that young adults have very little knowledge on the use of Smartphone technology for weight loss but would like to use this type of technology to help them lose weight. Results also indicated that young adults struggle to make healthy food choices and have priorities that outweigh exercise and they need support and guidance to make better decisions. In conclusion, young adults would be open to using Smartphone technology for weight loss but also need feedback and guidance to help make healthy decisions.